PTU-093 Inappropriate inflammatory responses in the ileum of ulcerative colitis patients. (28th May 2012) - Landy, J; Al-Hassi, H O; Peake, S T; English, N; Ciclitira, P J; Nicholls, R J; Clark, S K; Knight, S C; Hart, A L
Abstract : Introduction: Inflammation in ulcerative colitis (UC) is restricted to the colon. However, up to 50% of UC patients develop inflammation of the small bowel following restorative proctocolectomy (RPC). We hypothesised that in UC patients, ileal lamina propria dendritic cells would have a more "stimulatory" phenotype than in normal controls predisposing UC patients to pouch inflammation following RPC. Methods: Mucosal biopsy samples were taken from the ileum of UC patients undergoing RPC and from healthy controls undergoing colonoscopy. Lamina propria dendritic cells were isolated from biopsy tissue by collagenase digestion. DCs were identified as an HLA DR+, lineage- (CD3-, CD14-, CD16-, CD19-, CD34-, CD56-) population and expression of Toll-like receptors (TLRs), homing markers and co-stimulatory markers were measured by multicolour flow cytometry. T-tests were performed for statistical analysis. Results: There were no differences between the percentage of dendritic cells expressing TLR 2 (30.5±11.5% vs 32.5±8.8%) or TLR 4 (38.6±5.8% vs 38.8±7.2%) in the UC and healthy control ileum. A significantly greater percentage of lamina propria dendritic cells expressed the gut homing marker β7 in the normal ileum (33.8±9.6%) compared with the UC ileum (6.4±3.2%, p=0.007) as well as the co-stimulatory marker CD40 (80±2.9% vs 48.6±5.7%, p=0.001). Conclusion: Contrary to our expectations, lamina propria dendritic cells in the ileum of UC patients appear to have a less "stimulatory" phenotype than in normal controls. There may therefore be an absence of appropriate effector responses and reduced regulation by T-cells in the UC ileum. Further work is necessary to assess the T-cell responses to dendritic cell stimulation in the ileum of UC and in healthy controls. Competing interests: None declared.